Análise ex-ante do programa de transformação do aeroporto de Palmas-TO em aeroporto industrial - Moraes Junior, Helio Carneiro de (2025)
This paper analyzes, in an ex-ante manner, the Program for Transforming Palmas Airport into an industrial airport, based on John Kasarda's aerotropolis theory, highlighting the Industrial Airport model. The research identified structural challenges, such as inadequate infrastructure, low integration with production chains and insufficient economic incentives, and proposed a logical model divided into five phases: diagnosis, strategic planning, infrastructure development, implementation and initial operation, and expansion and consolidation. Each phase was detailed with specific actions, goals and performance indicators, allowing monitoring of progress and evaluation of results. In addition, the study emphasized the need for political coordination, robust strategic planning and public-private partnerships to make the project viable. It is concluded that the program has significant potential to boost the regional economy, attract investments, generate jobs and consolidate Palmas as a logistics-industrial hub, provided it is implemented in an integrated and efficient manner, based on clear parameters and continuous monitoring.